Human Being and Caliphate-oriented Ethics Bases of Imam Khomeini’s Mystical Ethics - Mahdi Baratifar; Hadi Vakili (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
According to the normative theories, one can speak of the three types of duty-based ethics, result-based ethics, and virtue-based ethics. A study of the history of Islamic rational-narrative traditions reveals the foundations and perspectives of all three types of ethics among Muslim thinkers. According to the authors, the fourth type of ethics can also be considered as “Caliphate-oriented ethics”, which is based on the assumption and succession between man and God, or in the sense of human Rabbi and Abd. In this article, we attempt to examine the concept of “Caliphate-based ethics” by examining the mystical ethics in the tradition of theoretical mysticism. According to the authors, (1) this type of ethics may be the correct interpretation of “mystical ethics” - in the tradition of theoretical mysticism attributed to Ibn al-Arabi; (2) Imam Khomeini’s mystical ethics is more compatible with “caliphate-based ethics” than other normative ethics theories; and (3) Caliphate-based ethics is subordinated to virtue ethics. In fact, the Caliphate’s ethics should be viewed as a virtue theory that differs in the nature of virtues, the method of recognizing virtues, and how to achieve virtues with conventional approaches to virtue ethics. In short, in this theory, virtues are the attributes of God, the method of recognizing virtues is the knowledge of the virtues, and the method of becoming virtuous is to imitate God and then become the caliph of God through mystical conduct in three stages. Purification, Polishing, and Adornation. In fact, it is this methodology of knowledge and moral development that is based on anthropology and mystical theology, which is found in the mystical works of the school of theoretical mysticism, including the mystical works of Imam Khomeini.